Comparison of heavy metal contamination in cropland soils adjacent to waste disposal site and other cropland soils in khulna, Bangladesh - Fahmida Akter Jolly; Debasish Pandit; Diponkor Adikari; Md. Khalid Saifullah; Gazi Tamiz Uddin; Syed Tanvin Abir; Ronjon Kumar; Amit Dutta; Rana Roy (Discover Sustainability)
Abstract Heavy metal contamination in Bangladesh has become widespread due to both industrialisation and natural geological processes, posing risks to public health and agriculture. This study aimed to assess the degree of heavy metal pollution in agricultural land of Khulna in Bangladesh, specifically comparing areas near a dumping site with the site further away. Soil samples were analysed for five heavy metals: zinc (Zn), copper (Cu), lead (Pb), cadmium (Cd), and iron (Fe), using indices like contamination factor (CF), pollution load index (PLI), geo-accumulation index (Igeo), and potential ecological risk index (PERI). We observed a significant variation (p < 0.05) in heavy metal concentrations between two sites. Pearson correlations indicated significant relationships among most metals in the near dumping site, suggesting that their concentrations tend to increase. The PLI showed lower pollution (PLI < 1) at the away site compared to the nearby. The CF values indicated moderate level of contamination (1 ≤ CF < 3) at the away site, while considerable contamination (3 ≤ CF < 6) was recorded at the near dumping site. The PERI were higher (95 ≤ PERI < 190) for near dumping site compared to the site away (PERI < 95), indicating a higher ecological risk at near dumping site. Igeo revealed moderate to strong pollution levels for Pb and Cd near the dumping site, whereas away site were unpolluted to moderately polluted. Overall, the findings highlighted cropland near dumping site experiences significantly higher heavy metal pollution than away site, underscoring the need for sustainable remediation and continuous monitoring to protect the environment and public health.